Beliefs about emotions as a transdiagnostic construct. Conceptualization in the cognitive-behavioural therapies - Sawicka, Monika J. (Przegląd Psychologiczny, 2022)
Aim The aim of the article is to discuss the concept of beliefs about emotions in the context of emotional regulation and conceptualization in different cognitive-behavioural therapy approaches. Theses The thesis is that beliefs about emotions are a transdiagnostic construct, meaning that their occurrence is not limited to specific nosological categories, and they influence the maintenance of symptoms across several classes of disorders, and they are measurable in both clinical and non-clinical populations. Conclusion The analysis of research results regarding the prevalence of negative beliefs about emotions in different groups allows for recognition of their transdiagnostic nature. In the first part, a comprehensive definition of the phenomenon and potential sources of its formation within cognitive and learning theories were presented. The factors mediating the relationship between beliefs about emotions and well-being were discussed, with particular emphasis on avoidance strategies. As a summary of these relationships, a general working model was proposed. In the second part, therapeutic procedures from the field of cognitive-behavioural therapy were presented as an approach with scientifically proven effectiveness. The application of these methods can directly or indirectly, through perpetuating factors, lead to a change in beliefs about emotions and contribute to the reduction of psychological and physical suffering.